The Rottweiler (CNIB, 2004)
The latest victim of 'the Rottweiler' was discovered very near Inez Ferry's antique shop in Marylebone. Someone spotted a shadowy figure running away but couldn't say for sure if it was a man or a woman. There were only two other clues: the murderer seemed to have a preference for strangling his victims and then removing something personal. 2003.

Thirteen steps down (CNIB, 2005)
Mix Cellini is superstitious about the number thirteen, and he is obsessed with 10 Rillington Place, where the notorious John Christie once committed a series of foul murders. He is also infatuated with a beautiful model who lives nearby, who would not look at him twice, while his landlady, Gwedolen Chawcer, is equally reclusive, living her life through her library. Both landlady and lodger inhabit weird worlds of their own, but when reality intrudes into Mix's life, a long pent-up violence explodes. 2004.